Cysteine and glutathione in catabolic conditions and immunological dysfunction - Dröge, Wulf (Current opinion in clinical nutrition & metabolic care, 1999)
The conspicuous increase in the plasma cysteine disulphide/thiol ratio in elderly persons and cancer patients indicates a shift of the plasma redox state. The most important redox buffers in skeletal muscle tissue and blood plasma, i.e. glutathione and albumin, respectively, are significantly decreased in different models of cachexia. Treatment with N-acetyl cysteine, i.e. a thiol-containing antioxidant, was found to increase the plasma albumin level and to ameliorate the loss of body cell mass in cancer patients and healthy individuals. The treatment of HIV infection with N-acetyl cysteine, in contrast, serves mainly as a tool to ameliorate the physiological and immunological consequences of the virus-induced cysteine deficiency.
Gesehen am 09.02.2021